Lipid oxidation dysregulation: an emerging player in the pathophysiology of sepsis - Muniz-Santos, Renan; Lucieri-Costa, Giovanna; Almeida, Matheus Augusto P. de; Moraes-de-Souza, Isabelle; Brito, Maria Alice Dos Santos Mascarenhas; Silva, Adriana Ribeiro; Gonçalves-de-Albuquerque, Cassiano Felippe (Frontiers in Immunology, 2023)
Sepsis is a life-threatening organ dysfunction caused by abnormal host response to infection. Millions of people are affected annually worldwide. Derangement of the inflammatory response is crucial in sepsis pathogenesis. However, metabolic, coagulation, and thermoregulatory alterations also occur in patients with sepsis. Fatty acid mobilization and oxidation changes may assume the role of a protagonist in sepsis pathogenesis. Lipid oxidation and free fatty acids (FFAs) are potentially valuable markers for sepsis diagnosis and prognosis. Herein, we discuss inflammatory and metabolic dysfunction during sepsis, focusing on fatty acid oxidation (FAO) alterations in the liver and muscle (skeletal and cardiac) and their implications in sepsis development.